Exploring psychosocial adaptation among people with chronic skin disease: A grounded theory study - Xiu‐jie Zhang; Hui Xu; Li Feng; Da‐qiu Wang; Ai‐ping Wang (Wiley, 2021)
Abstract Aim Chronic skin disease (CSD) often has devastating effects on the physiological, psychological and social aspects of patients, who must adapt to them. However, it is not clear how patients adapt, especially with regard to their psychosocial adaptation (PSA). This research explored a theoretical model of PSA among people with CSD. Design Following constructivist grounded theory methodology, a qualitative study was undertaken between August 2018 and June 2019. Methods Observation and semi‐structured interview were conducted with included participants (n=19). Data were iteratively coded and analyzed by constant comparison following the key stages of initial, focused, axial and theoretical coding until saturation was achieved. Results When individuals face the impacts of disease, they try to adjust to adapt it. The findings showed the core category (self‐cognitive) and the contributing categories (impacts of chronic skin disease, contextual factors, physiological experiences, psychological experiences, social experiences, and positive and negative psychosocial adaptations) of the PSA among people with CSD. The process of PSA among people with CSD was not linear throughout the disease and was instead entwined within a set of complexes (contextual factors‐experience) interactions. The consequences of PSA included positive and negative aspects. The theoretical model of PSA among people with CSD will provide us with information needed to develop accurate assessment and effective intervention strategies. Understanding that PSA among people with CSD is a complex, dynamic, and interactional process may provide evidence for further assessing and meeting the needs of people.